Hybrid Disk Drive Configuration on Database Server Virtualization - Ferdy Nirwansyah; Suharjito Suharjito (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
SSD is a revolutionary new storage technologies. Enterprise storage system using full SSD is still very expensive, while HDD is still widely used. This study discusses hybrid configuration storage in virtualized server database with benchmark against four hybrid storage configuration for four databases, ORACLE, SQL Server, MySQL and PostgreSQL on Windows Server virtualization. Benchmark using TPC-C and TPC-H to get the best performance of four configurations were tested. The results of this study indicate HDD storage configurations as visual disk drive OS and SSD as visual disk drives database get better performance as OLTP and OLAP database server compared with SSD as visual disk drive OS and HDD as a visual disk drive database. Based on the data research TPC-C, OLTP get best performance at HDD storage configurations as visual disk drive OS and SSD as a visual disk drives database and temporary files.